Menciptakan Sekolah Berkarakter - Elim Halimatusadiyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Character education is a central issue in Indonesian society, addressing concerns about educational inequality and the behavior of graduates. This article explores these issues and the diverse interpretations of the concept of